2019
DOI: 10.1212/nxg.0000000000000363
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy with migrating focal seizures

Abstract: ObjectiveTo report new sporadic cases and 1 family with epilepsy of infancy with migrating focal seizures (EIMFSs) due to KCNT1 gain-of-function and to assess therapies' efficacy including quinidine.MethodsWe reviewed the clinical, EEG, and molecular data of 17 new patients with EIMFS and KCNT1 mutations, in collaboration with the network of the French reference center for rare epilepsies.ResultsThe mean seizure onset age was 1 month (range: 1 hour to 4 months), and all children had focal motor seizures with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 39 publications
3
19
0
1
Order By: Relevance
“…These encompass an increase of excitability due to an increase of AP repolarization rate, a disinhibition due to a higher impact on inhibitory interneurons, an aberrant connectivity of neural networks linked to the impact of seizure in brain maturation, and molecular interactions in the C‐terminal part of the channels 8 . The distribution of the variants outside the C‐terminal region argues against the last hypothesis 3,16 . Our study identified a differential effect of the GOF of slack, with a stronger impact on GABAergic interneurons as compared to pyramidal neurons, which is in line with the disinhibition hypothesis 8,17 .…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…These encompass an increase of excitability due to an increase of AP repolarization rate, a disinhibition due to a higher impact on inhibitory interneurons, an aberrant connectivity of neural networks linked to the impact of seizure in brain maturation, and molecular interactions in the C‐terminal part of the channels 8 . The distribution of the variants outside the C‐terminal region argues against the last hypothesis 3,16 . Our study identified a differential effect of the GOF of slack, with a stronger impact on GABAergic interneurons as compared to pyramidal neurons, which is in line with the disinhibition hypothesis 8,17 .…”
Section: Discussionsupporting
confidence: 80%
“…8 The distribution of the variants outside the C-terminal region argues against the last hypothesis. 3,16 Our study identified a differential effect of the GOF of slack, with a stronger impact on GABAergic interneurons as compared to pyramidal neurons, which is in line with the disinhibition hypothesis. 8,17 Although pyramidal neurons are also affected, the impact on interneurons was higher regarding the maximum of the firing rate.…”
Section: F I G U R Esupporting
confidence: 86%
See 2 more Smart Citations
“…An additional patient with the same mutation and multi-drug refractory seizures has also been reported. 4,11,12 This patient was diagnosed at 12 years of age and has had a normal 24-hour Holter evaluation and has done well from a cardiac standpoint. An unspecified cardiac arrhythmia has been reported in a young patient with familial KCNT1 c.2782 C > T; p. Arg928Cys mutation.…”
mentioning
confidence: 99%